JARINGAN SOSIAL WACANA MAKAN BERGIZI GRATIS DI INSTAGRAM DALAM PERSPEKTIF PENTAHELIX - Arie Prasetio; Prasetya Yoga Santoso; Ridzki Rinanto Sigit (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2026)
This study examines the network structure of public discourse surrounding Indonesia’s Free Nutritious Meals program (Makan Bergizi Gratis/MBG) on Instagram using Social Network Analysis (SNA) within a Pentahelix framework. Background: MBG discourse on Instagram has become a contested arena between pro-government and critical coalitions, yet prior research has relied mainly on content or sentiment analysis, leaving the underlying network structure of actor influence unexamined. Methods: Data were collected through hashtag scraping (#makanbergizigratis) covering January–December 2025, yielding 106,513 posts from 114,003 accounts. Sixteen actors representing five Pentahelix elements were examined in Gephi across four centrality measures: degree, closeness, betweenness, and eigenvector. Results: The MBG discourse network forms a polycentric antagonistic scale-free structure, with @badangizinasional.ri functioning as the hegemonic nodal point (highest betweenness: 0.000317; eigenvector: 1.0), while @korelasimedia and @luarbioskop operate as counter-hegemonic nodal points. Government and media elements dominate the network, while community and academic actors remain structurally marginal. Conclusion: The MBG discourse network is structurally decentralized but not substantively democratized, challenging the normative assumption of Pentahelix as balanced multi-stakeholder collaboration. Implications: These findings substantiate Papacharissi’s contention that the networked public sphere does not necessarily produce democratization of public discourse, and point to the need for strengthening academic and community participation in digital policy communication.